THE EFFECT OF PERSON JOB FIT AND INTRINSIC MOTIVATION AND DISCIPLINE ON JOB SATISFACTION AND EMPLOYEE PERFORMANCE AT THE YOUTH AND SPORTS OFFICE OF EAST KUTAI REGENCY - Harmina Hawi; Sri Mintarti; Dirga Lestari (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study aims to analyze the influence of Person-Job Fit, Intrinsic Motivation, and Discipline on Job Satisfaction and its impact on the Performance of Employees of the East Kutai Regency Youth and Sports Office. In addition, this study examines the role of Job Satisfaction as a mediating variable between Person-Job Fit, Intrinsic Motivation, and Discipline with Employee Performance. The research method used is quantitative with the Structural Equation Modeling-Partial Least Squares (SEM-PLS) approach. The data was collected through a questionnaire distributed to employees of the East Kutai Regency Youth and Sports Office. The results of the analysis show that Person-Job Fit, Intrinsic Motivation, and Discipline have a positive and significant effect on Job Satisfaction and Employee Performance. Job Satisfaction also plays a mediator that strengthens the influence of these three variables on Employee Performance. These findings affirm the importance of human resource management that integrates appropriate work placement, internal motivation enhancement, and discipline enforcement to improve job satisfaction and employee performance. The practical implications of this research can be the basis for policies to improve employee management within the East Kutai Regency Youth and Sports Office.